2007
DOI: 10.5194/hessd-4-655-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precipitation and temperature ensemble forecasts from single-value forecasts

Abstract: Abstract. A procedure is presented to construct ensemble forecasts from single-value forecasts of precipitation and temperature. This involves dividing the spatial forecast domain and total forecast period into a number of parts that are treated as separate forecast events. The spatial domain is divided into hydrologic sub-basins. The total forecast period is divided into time periods, one for each model time step. For each event archived values of forecasts and corresponding observations are used to model the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 23 publications
1
94
0
2
Order By: Relevance
“…The conditional distribution of the forecasted variables is then fitted with the selected subset of the historical data of the forecasted variables. Schaake et al (2007) proposed a method to produce a probabilistic forecast from a deterministic and singlevalue forecast. We call this method the 'Deterministic to Probabilistic forecasts Conversion (DPC)' method.…”
Section: Methodsmentioning
confidence: 99%
“…The conditional distribution of the forecasted variables is then fitted with the selected subset of the historical data of the forecasted variables. Schaake et al (2007) proposed a method to produce a probabilistic forecast from a deterministic and singlevalue forecast. We call this method the 'Deterministic to Probabilistic forecasts Conversion (DPC)' method.…”
Section: Methodsmentioning
confidence: 99%
“…Further the uncertainties in the forecasts are generally greater than that associated with the observations. Statistical post-processing methods have been widely used to deal with the errors in QPFs and QTFs (Glahn and Lowry, 1972;Krzysztofowicz and Sigrest, 1999;Schaake et al, 2007). Data assimilation methods have been widely used to reduce the uncertainty associated with the initial conditions (ICs) used in the hydrological models.…”
Section: Uncertainties In Hydrological Forecastingmentioning
confidence: 99%
“…The approach presented here has some similarities to the method described first by Schaake et al (2007), which was then further improved by Wu et al (2011), in the sense that it portions the historical observed and corresponding forecasted data into four sub-regions to estimate the uncertainty of the rainfall forecast and provide a probabilistic hydrological forecast.…”
Section: Introductionmentioning
confidence: 99%